Training on Canva Application to Enhance Digital Learning Programs in High Schools - Putri, Helena Anggraeni; Astiwi, Wuri (Journal of Social and Community Development, 2025)
This activity aims to enhance teachers' skills in applying creative and innovative teaching methods and provide training on developing instructional media using the Canva application. The training, attended by 18 teachers from Muhammadiyah Mlati Senior High School, includes well-planned stages: thorough planning, needs assessment, meticulous preparation, effective implementation, and careful evaluation. Scheduled to take place on July 10-11, 2024, the training seeks to enable teachers to maximize the use of Canva in education, particularly in archiving evaluation programs and student assessments. The results of this activity are reflected in the significant improvement in the average pretest score from 67,11 to 87,44, as well as an n-Gain test score of 0,62, indicating a moderate level of achievement. This outcome demonstrates that the community service initiative was successfully executed and is expected to have a positive impact on the advancement of digitalized learning at Muhammadiyah Mlati Senior High School.